RELATIONSHIP OF WORKLOAD WITH WORK STRESS AMONG NURSES DURING THE COVID-19 PANDEMIC IN EAST LOMBOK DISTRICT - Alipurman, Agusnawadi; Sastrawan, Sastrawan (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Nurses as the front line in dealing with COVID-19 are at risk of contracting COVID-19 along with the current increase in COVID-19 cases. Nurses is carrying out their work because they have pressures that have an impact on their physical, mental and social conditions, causing work stres. Purpose: To determine the relationship between workload and work stress of nurses during the COVID-19 pandemic in East Lombok Regency. Method: This research was conducted in East Lombok Regency using quantitative analytic research with a cross-sectional study design. The population in this study were all nurses at the puskesmas in East Lombok Regency as many as 738 nurses. The sampling technique used a probability proportional size and obtained a sample of 77 nurses. Data collection uses an adoption questionnaire from Cooper and is collected online using Google Forms. Data processing and analysis, for bivariate analysis using the Chi-Square test with = 0.05. Result: Nurses with heavy workloads and experiencing heavy work stress were 45.5%, nurses with light workloads and experienced light work stress were 10.4%. The results of the analysis using Chi-Square obtained a p-value of 0.000 < α=0,05 with an OR of 5.5. Conclusion: Shows there is a relationship between workload and work stress of nurses in East Lombok Regency where the results of bivariate analysis obtained p-value 0.000 <0.05 and it is known that the OR value in this study is 5.5 which means nurses have a high workload and are at risk of experiencing stress. 5.5 times higher workload compared to nurses who have a low workload.